1992
DOI: 10.1128/jb.174.10.3370-3376.1992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inducing expression of cloned genes for the F0 proton channel of the Escherichia coli F1F0 ATPase

Abstract: To evaluate whether expression of cloned genes for the Fo proton channel of the Escherichia coli F1F0 ATPase is sufficient to cause membrane proton permeability, plasmids carrying different combinations of the uncB, E, and F genes, encoding the a, c, and b subunits of the Fo sector, cloned behind the inducible lac promoter in pUC9 or pUC18, were constructed. The effects of inducing Fo synthesis in an unc deletion strain were monitored by measuring cell growth rate, quantitating Fo subunits by immunoblotting, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The plasmid pTR-hF1Fo (ϩi) was used for transformation of an F1Fo-deficient E. coli strain, JM103⌬(uncBuncD) (hereafter, JM103⌬unc) (39). The transformants were aerobically grown in 2ϫYT medium supplemented with 100 g/ml ampicillin for 21 h. In the case of transformants harboring pSTV28 derivative plasmid (mentioned later), 30 g/ml chloramphenicol was also supplemented to maintain the plasmid in the cells.…”
Section: Preparation Of Membrane Vesicles and The Hybrid F1fomentioning
confidence: 99%
“…The plasmid pTR-hF1Fo (ϩi) was used for transformation of an F1Fo-deficient E. coli strain, JM103⌬(uncBuncD) (hereafter, JM103⌬unc) (39). The transformants were aerobically grown in 2ϫYT medium supplemented with 100 g/ml ampicillin for 21 h. In the case of transformants harboring pSTV28 derivative plasmid (mentioned later), 30 g/ml chloramphenicol was also supplemented to maintain the plasmid in the cells.…”
Section: Preparation Of Membrane Vesicles and The Hybrid F1fomentioning
confidence: 99%
“…1. With the exception of the Fo+8 plasmids, these plasmids were described previously (13). pRM1 contains all the genes (uncBEF) for the Fo sector in addition to the gene for the 8 subunit of F1 (uncH).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids pEA5, pWSB30.0, and pWSB33 were described previously (13,22). pRM1, which carries the Fo genes plus uncH (S subunit) cloned behind the lac promoter, was constructed by digesting pWSB30.0 with HindIll and EcoRI and ligating the resulting fragments with the pUC9 (23) vector, which had been digested with HindIIl and EcoRI.…”
Section: Methodsmentioning
confidence: 99%
“…,Brusilow and coworkers (1,16) have suggested that the a and 8 subunits act not upon assembly of Fo but upon activation of proton translocation.…”
mentioning
confidence: 99%
“…In Escherichia coli FIFO ATP synthase, the 8 subunit is required for the binding of F1 to Fo (1,8,9,14,16,17). A narrow stalk connecting the two sectors is thought to consist of the Fo b subunits and possibly F1 subunits, including the 8 subunit (5).…”
mentioning
confidence: 99%